Viral Replication - Rosas-Acosta, German (IntechOpen, 2013)
This book provides a collection of in-depth reviews broadly related to the mechanisms of viral replication as applied to various viruses of critical relevance for human or animal disease. Specifically, this book contains six different chapters: 1) Influenza A Virus Multiplication and the Cellular SUMOylation System; 2) West Nile Virus: Basic Principles, Replication Mechanism, Immune Response and Important Genetic Determinants of Virulence; 3) Hepatitis B Virus Genetic Diversity: Disease Pathogenesis; 4) An Overview of the Immune Evasion Strategies Adopted by Different Viruses With Special Reference to Classical Swine Fever Virus; 5) Viral Replication Strategies: Manipulation of ER Stress Response Pathways and Promotion of IRES-Dependent Translation; 6) Antiviral Replication Agents. This book is aimed at students, scholars, professors, and investigators who are peripherally related to, or somehow intrigued by, the different areas of virology covered in this book, as well as at those individuals with greater expertise and knowledge in the topics herein presented who may want up-to-date in depth reviews related to such topics.